(untitled) (مجلة المنصور, 2022)
This research entitled " The idea of Exceptional Circumstances and Their Applications in Iraqi Constitutions " isolates the state in which one of the public power by passes its assigned jurisdictions granted to it by the constitution by virtue of the occurrence of an exceptional state of condition that urges the Constitution to grant, the same power, wider authority which it does not enjoy in ordinary circumstances, a thing which results in some consequences that affect society . Here it is the duty of the law to reconcile the requirements of keeping pubic order at all times and in all conditions to the act of maintaining public rights and freedoms lest should squandered. Having suggested the broad outline of the organizing idea already mentioned, the researcher tried to state the most important applications of exceptional circumstances in the texts of Iraqi Constitutions in terms of the power enjoying exceptional jurisdiction, the extent of the success of other powers in guaranteeing that these judicial provisions are not to be exploited for purely aims and also in terms of the workability of onchecking that obtains in some Iraqi Constitutions in this respect. Unfortunately the researcher has found out that the Iraqi Constitutional system lacks a lot of regulations, a thing which makes of the idea of exceptional circumstances a purely legal idea not liable to be practiced for political aims, nor firmly establishing the footing of one power at the expense of the remaining powers. Though the idea of the research has some sort of political dimension, yet as far as Iraqi Constitutions are concerned, things have gone to the extreme . The basic aim of this unsophisticated study is to try to enrich the Iraqi Constitutional Library with the most important jurisdictions and topics relevant to Iraqi Constitution and to have some insightful look at the constitutional approach adopted by Iraqi Constitutions in the realm of Constitutional topics of ideas and with the purpose of enhancing the Iraqi Constitutional experience and of participating in amending its wrong directions and solidifying its staid legal actions .